Impact of attitudes and beliefs on antiretroviral treatment adherence intention among HIV-positive pregnant and breastfeeding women in Zambia - Jerry John Nutor; Jaime C. Slaughter-Acey; Shannon P. Marquez; Rose Ann DiMaria-Ghalili; Florence Momplaisir; Kelechi Elizabeth Oladimeji; Loretta S. Jemmott (BMC, 2020)
Abstract Objective The aim of this study was to investigate if attitudes or behavioral beliefs about antiretroviral therapy (ART) influence ART adherence intention among pregnant and breastfeeding women in Zambia. Methods We recruited 150 HIV-positive women receiving ART in urban (Lusaka) and rural (Sinazongwe) districts of Zambia. Generalized modified Poisson regression models were used to assess the extent to which adherence intention was influenced by attitude toward ART or behavioral beliefs about ART. Results Intention to adhere to ART differed significantly by income, knowledge about HIV transmission, attitudes, and behavioral beliefs (all Ps < .05). In addition, strong intention to adhere to ART differed by urban (69%) and rural (31%) place of residence (P ≤ .01). In adjusted models, women in the weak adherence intention group were more likely to be older, have less knowledge about HIV transmission, and have a more negative attitude toward ART (PR 0.74; 95% CI 0.67-0.82). Behavioral belief about ART, however, was significant in unadjusted model (PR 0.85; 95% CI 0.76-0.94) but not significant after adjusting for covariates such as age, knowledge of transmission, and district locality. Conclusion Compared to behavioral beliefs, attitudes about ART were more influential for intention to adhere. This knowledge will help inform effective and appropriate ART counseling for pregnant and breastfeeding women at different points along their ART time course.